Odpowiedzi

2009-11-04T22:10:04+01:00
A]3½×[-2⅓]=-⁷/₂×⁷/₃=-⁴⁹/₆=-8⅙ b]-5¼×[-2³/₇]=+²¹/₄×¹⁷/₇=12¾ c]-3²/₇:2⅓=-²³/₇׳/₇=-1²⁰/₄₉ e]-9⁴/₁₅:[-¹³⁹/₁₅]=+¹³⁹/₁₅×¹⁵/₁₃₉=1
Najlepsza Odpowiedź!
2009-11-04T22:11:50+01:00
A)3½ ×(-2⅓)=7/2 *(-7/3)=-49/6=-8 i 1/6
b)-5¼.(-2³/₇) =-21/4*(-17/7)=51/4=12 i 3/4
d)-3²/₇:2⅓ =-23/7:7/3=-23/7*3/7=-69/49=-1 i 20/49
e)-9⁴/₁₅:(-¹³⁹/₁₅)=-139/15*(-15/139)=1
2009-11-04T22:12:19+01:00
A)=7/2*(-7/3)=-49/6=-8 1/6
b)=-21/4*(-17/7)=51/4=12 3/4
d)=-23/7*3/7=-69/49=-1 20/49
e)=-139/15*(-15/139)=1